2017
DOI: 10.1007/s12035-017-0580-9
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Proteomic Analysis Reveals Distinct Pathway Deregulation Profiles at Early and Late Stages in a Rat Model of Alzheimer’s-Like Amyloid Pathology

Abstract: The cerebral accumulation and cytotoxicity of amyloid beta (Aβ) is central to Alzheimer's pathogenesis. However, little is known about how the amyloid pathology affects the global expression of brain proteins at different disease stages. In order to identify genotype and time-dependent significant changes in protein expression, we employed quantitative proteomics analysis of hippocampal tissue from the McGill-R-Thy1-APP rat model of Alzheimer-like amyloid pathology. McGill transgenic rats were compared to wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 142 publications
0
15
0
Order By: Relevance
“…Our laboratory has developed tg lines expressing human APP with the double Swedish and the Indiana mutations under the Thy1 promoter, which recapitulate key features of the AD-like amyloid pathology in mice and rats. The McGill-Thy1-APP mice (Ferretti et al, 2011) and McGill-R-Thy1-APP rats (Leon et al, 2010) have been extensively studied by us (Cuello et al, 2010, 2012; Ferretti et al, 2012a,b; Hanzel et al, 2014; Iulita et al, 2014, 2017; Pimentel et al, 2015; Do Carmo et al, 2016, 2018; Wilson et al, 2017a,b, 2018; Hall et al, 2018) and others (Nilsen et al, 2012, 2014a,b; Galeano et al, 2014, 2018; Qi et al, 2014, 2018; Heggland et al, 2015; Martino Adami et al, 2017a,b; Parent et al, 2017; Zhang et al, 2017; Prestia et al, 2018). In the following section, we will discuss the particular value of these specific models in experimental pharmacology.…”
Section: Pharmacological Therapy In Mouse and Rat Models Of The Ad-limentioning
confidence: 99%
“…Our laboratory has developed tg lines expressing human APP with the double Swedish and the Indiana mutations under the Thy1 promoter, which recapitulate key features of the AD-like amyloid pathology in mice and rats. The McGill-Thy1-APP mice (Ferretti et al, 2011) and McGill-R-Thy1-APP rats (Leon et al, 2010) have been extensively studied by us (Cuello et al, 2010, 2012; Ferretti et al, 2012a,b; Hanzel et al, 2014; Iulita et al, 2014, 2017; Pimentel et al, 2015; Do Carmo et al, 2016, 2018; Wilson et al, 2017a,b, 2018; Hall et al, 2018) and others (Nilsen et al, 2012, 2014a,b; Galeano et al, 2014, 2018; Qi et al, 2014, 2018; Heggland et al, 2015; Martino Adami et al, 2017a,b; Parent et al, 2017; Zhang et al, 2017; Prestia et al, 2018). In the following section, we will discuss the particular value of these specific models in experimental pharmacology.…”
Section: Pharmacological Therapy In Mouse and Rat Models Of The Ad-limentioning
confidence: 99%
“…Furthermore, this approach opened a window of opportunity for studying putative compensatory mechanisms following RyR2 dysregulation. This was important because, apart from post-translation modifications of RyR2 [26], downregulation of RyR2 expression levels was observed in both, humans samples [28,39] and an animal model of Alzheimer's disease [38]. Following acute RyR2 deletion, we observed compensatory changes on two levels.…”
Section: Discussionmentioning
confidence: 85%
“…This approach enabled us to investigate the acute effects of RyR2 deletion on spine density gaining insight into putative compensatory mechanisms. Since altered regulation of RyR2 expression has been observed in pathological conditions such as Alzheimer's disease [28,38,39], the observation of compensatory mechanisms on the level of neuronal excitability, neuronal morphology and network function might provide important pathophysiological insights. Thus, we unilaterally injected either rAAV.…”
Section: Acute Ryr2 Knockout Leads To Reduced Spine Densities Reducementioning
confidence: 99%
“…It has been reported that Aβ plaques are present in the brain of approximately one-third to one-half of individuals aged ≥65, and tau inclusions are present almost universally (30). In AD, APP is cleaved by β-secretase and γ-secretase to produce toxic Aβ protein, which is involved in plaque formation (31). In the present study, vildagliptin was demonstrated to significantly reduce APP and p-tau protein expression, with this effect being more pronounced at the higher 10 mg/kg vildagliptin dose.…”
Section: Discussionmentioning
confidence: 99%